Direito à nacionalidade, direito fundamental: a apatridia e a competência atributiva da ONU - Marco, Carla Fernanda de (2008)
This present study deals with the legal institution of nationality as a fundamental human right, considering that the right to nationality is protected by the State both in the domestic and international spheres, pursuant to the international rules aimed at protecting the human being, entered into between sovereign States. The study is opened with the concept of nationality and other related matters, such as nation and citizenship. The initial approach refers to the rules of nationality and citizenship within Brazilian law, the basis of which are the constitutional and statutory principles and rules, as well as both Brazilian and comparative case law. The right to nationality is analyzed also under the rules of international protection of human rights, whose main objective is to demonstrate the affirmation of the right to nationality as a right inherent to all human beings. In this sense, one must inevitably consider the problem faced by the nationless. Following, one examines the principles inherent to Brazilian Constitutional Law and Public International Law that are applicable to nationality, the main approach of which is the constitutional principle of the precedence of human rights in Brazil as regards its international relationships. Thus, one attempts to demonstrate the need to combine the rules governing the domestic law and those governing the international law so as to preserve the fundamental right to nationality. One highlights the hierarchical rank of the international rules aimed to protect the human rights in Brazil, and finally, the fundamental role of the United Nations in the security and efficiency of said international norms designed to protect the fundamental right to nationality